Hazard assessment of storm events for the portuguese northern coast - Gomes, Mariana Peixoto (2018)
Coastal zones currently face severe weaknesses and are subject to high-risk situations. Tropical storm events can contribute to the occurrence of these high-risk situations by causing storm surges with high water levels and, consequently, episodes of wave-overtopping and coastal flooding. This work considers a series of storm scenarios and analyzes their impacts through numerical modelling. Firstly, historical storm tracks and intensities are characterized for the Portuguese northern coast in terms of probability of occurrence. Secondly, several storm events with a high potential of occurrence are generated using a specific tool of the DelftDasboard interface for Delft3D software. Hydrodynamic models are then used to generate an ensemble of simulations to assess the storms? effects on coastal water levels. Based on the statistical data of the numerical modeling results, a synthesis of the coastal storms? impacts at different locations within the study area is performed. Depending on the storm category, surge heights can reach 1.10 meters above tide levels under simulated conditions on the Portuguese northwestern coast.